Aristotle on μετὰ λόγου capacities and voluntary animal locomotion. Part two: freedom, scientific knowledge and voluntary locomotion - Nascimento, Daniel Simão (Revista Archai, 2025)
According to the dominant interpretation of the distinction between capacities that are “without-λόγος” (ἄλογοι) and capacities that are “with-λόγος” (μετὰ λόγου, Metaph. 9.2 1046a34-b2), the latter would be unique to human beings. We can find four arguments in defense of that thesis in the secondary bibliography. In a previous paper I dealt with two of these arguments, which I called the psychic arguments. This article deals with the other two and presents a positive argument for the alternative reading that tries to make it seem plausible - although not unassailable - in light of its own merits. According to this alternative reading, it is with the framework provided by Aristotle to explain the functioning of bidirectional capacities that we must explain the functioning of the capacity responsible for producing voluntary locomotion in all animals.